Weapons from the Ridkivtsi archaeological complex (eighth–eleventh centuries) - Калініченко, Віталій; Пивоваров, Сергій (Lodz, Lodz University Press, 2026)
Weapons constitute one of the most striking and important categories of archaeological finds from the Middle Ages. They serve as a valuable source for studying various aspects of the history of the population of Central and Southeastern Europe. Furthermore, weapons are a crucial chronological indicator; their typological characteristics and associated artefacts provide insights into the military-political history of populations across different regions. A substantial collection of weapons, encompassing both close-combat and long-range types, as well as equestrian equipment, was unearthed during excavations at the Rydkivtsi archaeological complex. These finds include over 100 arrowheads, parts of quivers, darts, axes, spurs, elements of horse equipment, and fragments of chain mail, among others. Collectively, the weapons from the settlement are vital for reconstructing the military and political history of the region during the 9th–10th centuries. They attest to the developed military culture of the local populace and suggest the presence of a nomadic substratum within the settlement's structure.
Weapons from the Ridkivtsi archaeological complex (eighth–eleventh centuries)
Keywords: археологічні дослідження; Буковина; середньовіччя; наконечники стріл; Рідківецький археологічний комплекс; Україна; предмети озброєння; шпори; озброєння